Acute Viral Hepatitis C-Induced Jaundice in Pregnancy - Tsung-Ying Hsieh; Chen-Hsiang Yu; Pao-Lin Kuo; Fong-Ming Chang (Taiwanese Journal of Obstetrics & Gynecology, 2006)
Objective: Acute viral hepatitis C-induced jaundice in pregnancy is very rare and may be fatal. Here, we report a complicated case with acute hepatitis C-induced jaundice in pregnancy with successful management Case Report: A 27-year-old pregnant woman, gravida 2, para 1, with gestational age of 36 weeks and 5 days, was referred to our hospital due to jaundice and elevated liver enzymes of undetermined cause. She had been suffering from general weakness, diarrhea and vomiting for 1 week, and jaundice with tea-colored urine for 3 days. At our medical center, acute viral hepatitis C-induced jaundice was suspected. Since her general condition deteriorated at 36 weeks and 6 days of gestation, we decided to induce labor. A male baby was born smoothly via the vaginal route, with birth weight 2,857 g, birth length 48.6 cm, and 1- and 5-minute Apgar scores of 7 and 9, respectively. Maternal condition improved dramatically after delivery and her serum liver enzymes and bilirubin levels gradually approached normal ranges. Conclusion: Mothers and fetuses with acute viral hepatitis C-induced jaundice during pregnancy are at great risk of mortality and morbidity. Timely termination may be one of the choices of treatment when fetal maturity has been reached and the maternal condition has deteriorated.